Microalbumin: Urinary Biomarker of Cardiovascular Risk Assessment - Samad, Tabassum; Haque, Wasim Md Mohosin ul (BIRDEM Medical Journal, 2016)
Microalbuminuria is an early sign of vascular damage. Now-a-days it is considered as a predictor of worse outcome for both renal and cardiac patients. In this review we investigate the magnitude of relationship between microalbuminuria and incident coronary heart disease and mortality. Microalbuminuria is an independent predictor of coronary heart disease and all cause mortality. It is demonstrated that cardiovascular and renal risk is elevated even in the high normal range of microalbuminuria. Early detection of microalbuminuria, or therapies that prevent or delay the development of microalbuminuria, and all measures that prevent it, may help to prevent or delay cardiovascular events Birdem Med J 2015; 5(2): 98-103